AN ANALYSIS OF STUDENTS’ ERRORS IN TRANSFORMING ACTIVE TO PASSIVE SENTENCE - Septianasari, Lina (English Education Department of STKIP Pasundan, 2019)
Passive voice is one of the important English grammar that should be mastered because it is used at formal and informal communication. The EFL students tend to produce grammatical errors in transforming active to the passive sentence because of syntactical interference of their first language. The objectives of this research are to know the types of errors that students made in transforming active to passive sentences, to know the students' problems in transforming active to passive sentences and to know the proportion of the students' errors. The subject of this research is 20 English students at one private university in Lampung. The result of this research shows that the total number of errors that had been committed by the students based on surface strategy taxonomy is 280 errors, which falls into the following proportion of the four kinds of errors in surface strategy taxonomy: 126 errors of omission error, 18 errors of addition error, 120 errors of misformation error, and 16 errors of misordering error.